Analysis of Speech Act of Instant Noodle Advertisement 50th on Television - Moch. Idham Fadlilah (Universitas Muhammadiyah Barru, 2022)
Advertising is a form of displaying messages by non-personal communicators through the media to audiences in exchange for consideration. In other words, advertising is a form of impersonal presentation and promotion of ideas, goods, or services advertised by a particular sponsor and for which consideration must be paid. Some interpret from a purely communication, advertising and marketing point of view, others from a psychological point of view. The communication perspective tends to emphasize the process of delivering messages from the communicator to the audience. From an advertising perspective, the emphasis tends to be on aspects of delivering creative and persuasive messages delivered through special media. The marketing perspective emphasizes the importance of advertising as a marketing tool, namely selling products. Speech act events are usually useful for confirming certain information. Speech act events are characterized by the presence of speakers and speech partners. The problems studied in this analysis are speech acts, idioms, utterances, and phrases contained in television advertisements for an instant noodle products. This research is important because in production, promotion is one of the important aspects to boost product sales. A qualitative descriptive method with a pragmatic approach was used to conduct this research. The data for this study were generated and analyzed using the instant noodle advertising language. Data collection techniques used are observation and note-taking techniques. Data is obtained by viewing and monitoring it. The instant noodle advertisements and recording data from selected advertisements for study. The results of this study indicate that there are verbal speech acts, nonverbal speech acts, and verbal speech acts.